The Mardians: a Note - Gregoratti, Leonardo (Anabasis. Studia Classica et Orientalia, 2014)
The Mardians were an Iranian mountain tribe which inhabited many different regions of the Near East. Despite the fact that they are frequently present in the narratives of both Greek and Roman historians, they never aroused much interest among scholars. This contribution remains the only attempt to put together all the references concerning the Mardians, providing at the same time some general hypothesis about their apparent geographical diffusion. It cannot be excluded that the Roman authors who introduced the Mardians among the enemies the imperial armies had to face in their eastern campaigns, wanted to establish a historical link between the current events and Alexander’s campaigns.